Electromagnetic noise suppression characteristics of a coplanar waveguide transmission line integrated with a magnetic thin film - Sohn, Jaecheon; Han, S. H.; Yamaguchi, Masahiro; Lim, S. H. (AMER INST PHYSICS, 2006)
Integrated-type electromagnetic noise suppressors based on a coplanar waveguide transmission line, incorporated with a SiO2 dielectric and a nanogranular Co-Fe-Al-O magnetic thin film with excellent high frequency soft magnetic properties, are reported. A systematic study on the frequency dependences of scattering parameters, power loss, and phases of transmitted and reflected signals as a function of the length and width of the magnetic thin film indicates that the main loss mechanism of the integrated devices is the L-C resonance. Excellent noise suppression characteristics, combined with a resonance frequency of several gigahertz, are achieved in the present integrated devices. (c) 2006 American Institute of Physics.